Kasaysayang panlipunan ng Maynila, 1765-1898 - Camagay, Maria Luisa T. 4 0 16; 5 (Quezon City,Philippines : [Toyota Foundation], 1992)
History of social condition in Manila, 1765-1898.
Includes bibliographical references (p. 231-244).
In Tagalog.
Keywords: 2 -- 0; 6; 20; Social conditions.;Social conditions. -- Manila (Philippines);Manila Metropolitan Area (Philippines) -- 20; 2